2007
DOI: 10.1105/tpc.106.046573
|View full text |Cite
|
Sign up to set email alerts
|

The Thylakoid Lumen Protease Deg1 Is Involved in the Repair of Photosystem II from Photoinhibition in Arabidopsis

Abstract: Deg1 is a Ser protease peripherally attached to the lumenal side of the thylakoid membrane. Its physiological function is unknown, but its localization makes it a suitable candidate for participation in photoinhibition repair by degradation of the photosystem II reaction center protein D1. We transformed Arabidopsis thaliana with an RNA interference construct and obtained plants with reduced levels of Deg1. These plants were smaller than wild-type plants, flowered earlier, were more sensitive to photoinhibitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
172
2
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 188 publications
(186 citation statements)
references
References 41 publications
(51 reference statements)
8
172
2
2
Order By: Relevance
“…Specifically, it was demonstrated for AtDeg1, 7 and 8 that recombinant versions of these enzymes catalyze in vitro degradation of photodamaged PSII reaction center protein PsbA (D1) which in vivo is inherent to PSII repair cycle. The results have suggested that the photodamaged PsbA protein is cleaved in vivo by introduction of multiple cuts by cooperating AtDegs 1, 5/8, 7 and probably AtDeg2 as well [12,[14][15][16][17]. Similarly, recombinant version of AtDeg1 and AtDeg7 has been demonstrated to be responsible for in vitro degradation of PsbD, PsbS, Lhcb4 and cytb6 as well as PsbB-D, respectively under photoinhibitory conditions [12,18].…”
Section: Introductionmentioning
confidence: 92%
“…Specifically, it was demonstrated for AtDeg1, 7 and 8 that recombinant versions of these enzymes catalyze in vitro degradation of photodamaged PSII reaction center protein PsbA (D1) which in vivo is inherent to PSII repair cycle. The results have suggested that the photodamaged PsbA protein is cleaved in vivo by introduction of multiple cuts by cooperating AtDegs 1, 5/8, 7 and probably AtDeg2 as well [12,[14][15][16][17]. Similarly, recombinant version of AtDeg1 and AtDeg7 has been demonstrated to be responsible for in vitro degradation of PsbD, PsbS, Lhcb4 and cytb6 as well as PsbB-D, respectively under photoinhibitory conditions [12,18].…”
Section: Introductionmentioning
confidence: 92%
“…The resulting interstage repair complex is presumably similar to the CP43-less PSII complex RC47, which appears during biogenesis (14). The partial disassembly allows the removal of damaged D1, which is degraded mainly by FtsH protease in cyanobacteria, whereas in plants, several Deg proteases assist this process (15)(16)(17)(18). The new pD1 is cotranslationally synthesized into the D1-depleted PSII complex (19 -21), and the active holoenzyme is then reassembled similar to the biogenesis process.…”
Section: Photosystem II (Psii)mentioning
confidence: 99%
“…This explains the mechanism of the donor-side photoinhibition of PSII. More recently, it was also suggested that lipid peroxidation induced by strong illumination accelerates the damage Historically, the Deg protease was first proposed as a protease candidate [31,37,38,47], but there has been controversy over the exact roles of Deg and FtsH in the proteolytic process of the photodamaged D1 protein [32,[48][49][50]. The discussion on this issue is ongoing with newly obtained data.…”
Section: Damage and Degradation Of The D1 Protein Under Light And Heamentioning
confidence: 99%
“…Initially Deg proteases, which are the other prokaryotic proteases found in cyanobacteria and higher plant chloroplasts, were the most promising protease candidate [31]. Through this and other related works, the D1 protein was suggested to be degraded first by Deg proteases [31], then further degraded by FtsH proteases [36,37]. The FtsH proteases were then suggested as the proteases responsible for the primary cleavage of the D1 protein [35,45].…”
Section: Specific Roles Of Ftsh Proteases In the Cyanobacteria And Chmentioning
confidence: 99%
See 1 more Smart Citation